Characteristics and Properties of Thai Forest Plantation Woods and Their Application in Creative Works - Sonsang, Suppapong; Tovivich, Supitcha (DEC Journal : Art and Design, 2025)
This research aims to study 1) knowledge, skills, and concepts in the entire process of forest plantation management, 2) characteristics and properties of plantation wood suitable for creative works, and 3) approaches to utilizing distinctive properties of plantation wood in various creative works. The study employs inductive research methodology, drawing general conclusions from multiple specific observations, combined with Participatory Action Research (PAR). Data was collected from relevant stakeholders including farmers, forest plantation entrepreneurs, forestry academics, and creative professionals through group meetings, workshops, and in-depth interviews. Data analysis was conducted using Conventional Content Analysis. The findings reveal that key knowledge in plantation wood management includes selecting appropriate tree species with diversity, correct species identification, proper planting and maintenance, and efficient harvesting and processing, along with clear purpose definition for wood utilization. Important characteristics and properties of plantation wood suitable for creative works include wood color shades and grain patterns from proper processing techniques, wood grade strength appropriate for specific uses, and natural dimensional stability and durability. The approaches to utilizing plantation wood’s distinctive properties vary by work type. Architectural works emphasize wood length, mechanical properties, and environmental durability. Product and furniture design focus on physical characteristics, appropriate wood hardness for tools and machinery, and variety of wood grain and color shades. While artistic crafts emphasize the natural beauty of wood species. Key findings highlight the necessity to develop a database of plantation wood properties at different ages, promote planting of market-demanded species, and establish networks connecting growers with creative professionals to promote efficient and sustainable utilization of plantation wood.